TINJAUAN YURIDIS TERHADAP KEABSAHAN PERJANJIAN PENGANGKATAN ANAK DI BAWAH TANGAN DALAM PERSPEKTIF HUKUM PERDATA INDONESIA - Lumbantobing, Yohana Putri Magdalena; Yudhistira, Eko (Sriwijaya Journal of Private Law, 2025)
In Civil Case No. 1/Pdt.G/2020/PN Blt, the Plaintiff came from Batam to Blitar city to meet the Defendants (husband and wife) who were known through Facebook and to follow up on the agreement. Furthermore, the Plaintiff felt regret and wanted to request that her child be returned to the Plaintiff. The objectives of this research are: to find out the juridical consequences of child adoption that is not in accordance with the law, the limits of the rights and responsibilities of single parents towards children who have been adopted with an agreement under the hand, and to find out the legal considerations used by the Panel of Judges regarding the validity of the Child Adoption Agreement under the hand and Granting child custody to adoptive parents based on Decision Number 1/Pdt.G /2020/PN Blt.The research conducted is normative legal research. Researchers use data collection tools in the form of literature studies or documentary studies. The approach used by researchers is the approach of legislation (The Statue Approach), and the case approach (Case Approach). The data analysis method used by researchers is qualitative data analysis which involves an assessment and understanding of legal aspects.The consequences of adopting a child that is not in accordance with the law are the rights and obligations of each party, between the adoptive parents and their adopted child cannot be sued. The limitation of the rights and responsibilities of biological parents towards children who have been adopted with an underhand agreement is that all rights and obligations of biological parents are transferred to adoptive parents. Except for adopted female children who are Muslims, if she is going to get married then the only person who can be her marriage guardian is her biological parents or blood relatives. The panel's consideration was correct. Because even though the agreement was made underhand, the parties involved still fulfilled the elements of the agreement as stipulated in the applicable law, but the adoptive parents still had to fulfill the procedure of legalizing the adoption of children through a court decision. The panel's consideration was correct. Because even though the agreement was made underhand, the parties involved still fulfilled the elements of the agreement as stipulated in the applicable law, but the adoptive parents still had to fulfill the procedure of legalizing the adoption of children through a court decision.